Copper-Catalyzed Asymmetric Carboboronation of Allenes to Access α-Quaternary Amino Esters with Adjacent Stereocenters - Chao-Yang Zhao (Cell Reports Physical Science, 2020)
Summary: Optically active α-quaternary amino acids have received much attention because of the important biomedical applications implicated for compounds containing this structure. Additionally, asymmetric synthesis of highly functionalized chiral α-quaternary amino esters with vicinal stereocenters by a single catalyst is still a great challenge due to the difficulty in stereocontrol of the configurations. Here, we develop a copper-catalyzed highly diastereo- and enantioselective three-component coupling of allenes, diboron, and ketiminoesters to access chiral quaternary amino esters with adjacent stereocenters. The stereochemical control is enabled by using bulky C2-symmetric N-heterocyclic carbene (NHC) as a chiral ligand. This protocol also features mild reaction conditions, wide substrate scope, and may subsequently have diverse applications in organic synthesis.